Anodic Cyclizations, Seven‐Membered Rings, and the Choice of Radical Cation vs. Radical Pathways1. Issue 7 (17th May 2019) - Perkins, Robert J.; Feng, Ruozhu; Lu, Qingquan; Moeller, Kevin D.
Summary of main observation and conclusion: While many steps in an oxidative cyclization reaction can be important, it is the cyclization step itself that plays the central role. If this step does not proceed well, then optimization of the rest of the sequence is futile. We report here that the key to the cyclization is channeling the reaction down the correct pathway. Some reactions require the use of a radical pathway and some require the use of a radical cation pathway. An example of each is provided along with a strategy for accessing both pathways using a common intermediate. Abstract : Anodic cyclization reactions can be channeled down one of two main pathways. This manuscript describes when to use each.